The Effect Of Price Perception, Location And Facility Perceptions On Purchasing Decisions (Survey On Consumers Of Mitra Mart Minimarkets) - Riska Faujiah; Budhi Wahyu Fitriadi; Barin Barlian (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of perceptions of price, location and facilities simultaneously and partially on purchasing decisions at Mitra Mart Minimarkets. The method used in this study is a quantitative research method with a causality method and a consumer survey approach with a sample of 100 respondents. The data were collected using questionnaire techniques. The data analysis used in this study used multiple linear regression analysis, correlation coefficient and coefficient of determination. The results showed that the perception of price, location and facilities had a significant simultaneous and partial effect on the purchasing decision of Mitra Mart Minimarket.